2006
DOI: 10.1074/jbc.m602551200
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosylation of Bcl-2 Inhibits Its Ubiquitin-Proteasomal Degradation

Abstract: Bcl-2 is a key apoptosis regulatory protein of the mitochondrial death pathway whose function is dependent on its expression levels. Although Bcl-2 expression is controlled by various mechanisms, post-translational modifications, such as ubiquitination and proteasomal degradation, have emerged as important regulators of Bcl-2 function. However, the underlying mechanisms of this regulation are unclear. We report here that Bcl-2 undergoes S-nitrosylation by endogenous nitric oxide (NO) in response to multiple ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 183 publications
(141 citation statements)
references
References 59 publications
4
134
0
3
Order By: Relevance
“…Bcl-2 levels are controlled by its rate of synthesis, as well as by its rate of degradation by the ubiquitin-proteasomal pathway. Azad et al 116 have demonstrated that NO causes Snitrosylation of Bcl-2 in the human lung cancer cell line NIH-H460 and this prevents the ubiquitin-proteosomal degradation of Bcl-2, thus increasing its level and preventing Cr(VI)-mediated apoptosis of these cells. Bcl-2 Snitrosylation occurs on cys 158 and cys 229 of this protein and is mediated by either endogenous production of NO or by addition using external donors.…”
Section: Bcl-2 S-nitrosylation and Cancer Cell Apoptosismentioning
confidence: 99%
“…Bcl-2 levels are controlled by its rate of synthesis, as well as by its rate of degradation by the ubiquitin-proteasomal pathway. Azad et al 116 have demonstrated that NO causes Snitrosylation of Bcl-2 in the human lung cancer cell line NIH-H460 and this prevents the ubiquitin-proteosomal degradation of Bcl-2, thus increasing its level and preventing Cr(VI)-mediated apoptosis of these cells. Bcl-2 Snitrosylation occurs on cys 158 and cys 229 of this protein and is mediated by either endogenous production of NO or by addition using external donors.…”
Section: Bcl-2 S-nitrosylation and Cancer Cell Apoptosismentioning
confidence: 99%
“…Dynamin also proved to be S-nitrosylated at C607 during endocytosis . On the other hand, NO also has anti-apoptotic function through S-nitrosylation of Bcl2, which inhibits ubiquitin-proteasomal degradation and thus inhibits apoptosis (Azad et al, 2006).…”
Section: Cell Death Signal Cascades Regulated By S-nitrosylationmentioning
confidence: 99%
“…S-nitrosylation of Bcl-2 was measured as previously described (15). In brief, cells were treated, harvested, lysed, and subjected to immunoprecipitation as described previously here.…”
Section: Measurement Of Bcl-2 S-nitrosylationmentioning
confidence: 99%